2020
DOI: 10.1159/000508447
|View full text |Cite
|
Sign up to set email alerts
|

Hepcidin Status at 2 Months in Infants Fed Breast Milk Compared with Formula

Abstract: <b><i>Introduction:</i></b> The basis for the superior absorption of iron from breast milk compared with infant formulas is unclear. The hormone hepcidin downregulates dietary iron absorption. Hepcidin production increases with increased body iron status (reflected in serum ferritin levels). We hypothesized that serum hepcidin levels are suppressed relative to iron status in infants fed breast milk compared with formula. <b><i>Methods:</i></b> Subjects were healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Additionally, the hormone lactoferrin, present in high concentrations in breast-milk, may contribute to increased iron absorption in infants [23,24]. A recent study showed that breast-milk-fed infants have lower levels of serum hepcidin than formula-fed infants, despite similar urinary ferritin levels [25]. Hepcidin is a hormone that has been shown to sequester iron in hepatocytes, diminishing the serum iron available for use in erythropoiesis [26,27].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the hormone lactoferrin, present in high concentrations in breast-milk, may contribute to increased iron absorption in infants [23,24]. A recent study showed that breast-milk-fed infants have lower levels of serum hepcidin than formula-fed infants, despite similar urinary ferritin levels [25]. Hepcidin is a hormone that has been shown to sequester iron in hepatocytes, diminishing the serum iron available for use in erythropoiesis [26,27].…”
Section: Discussionmentioning
confidence: 99%
“…Contrary to this, Dewan et al [14] concluded that serum hepcidin is not useful to detect IDA in infants but instead suggested that the predictive value for IDA was higher from urinary Hepcidin. Reference ranges for Hepcidin at different ages have been suggested but there is a lack of standardized laboratory methods and the ranges diverge [8 & , [15][16][17][18]. Another more recently suggested biomarker is reticulocyte Hb (Chr).…”
Section: Iron Status Biomarkersmentioning
confidence: 99%
“…There are differences in the absorption and utilization of iron in the nursing infant compared to the formula fed infant with varying intestinal iron binding mechanisms and iron binding proteins. Additionally, the premature infant may have different iron absorptive mechanisms and risk factors compared to the term infant [44,[69][70][71][72][73][74][75].…”
Section: Iron Transport In the Infant Gutmentioning
confidence: 99%
“…It is suggested that iron redistribution may occur in the gastrointestinal tract such that most iron is incorporated into lactoferrin [44], unique iron absorption by a specific receptor in the small intestine of newborn infants is proposed [66,70]. A recent study found that urinary hepcidin levels in infants fed breastmilk compared to formula were lower, suggesting that the lower infant hepcidin levels contribute to milk iron bioavailability [71].…”
Section: Iron Transport In the Infant Gutmentioning
confidence: 99%